Implementasi Telepon Seluler sebagai Kendali Lampu Jarak Jauh - Filiardian Setiady, Iswanto , Agus Jamal , (Semesta Teknika, 2011)
The bustle and activity of our daily erratic make us do not know when it comes to the house, where the lights are supposed to be lit. But it was not turned on because no one was home. This certainly makes us into a panic and anxiety, because it will not start from where we are. Another example is in the office, on the road, and anywhere at the time the house empty or unoccupied. From some of the problems mentioned above, the study sought to realize one of the benefits of the existing mobile phone. Utilization of it is to create a tool that can activate the light there at home by using a mobile phone channels. The system is able to turn on or turn off the lights even though the house empty or unoccupied by long distance. With this system we are and at anytime can menggendalikan home appliances remotely.